Sengketa Hak Asuh Anak di Pengadilan Agama: Rekonstruksi Prinsip Kepentingan Terbaik Anak Berbasis Pancasila dan Islamic Sociological Jurisprudence Theory - Evelyn Hatiku; Ismi Arinal Mufidati; Ayu Dwi Kusuma Wardani; Ahmad Muhamad Mustain Nasoha (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
Child custody disputes in Indonesia’s Religious Courts constitute a significant domain of Islamic family law, particularly given the escalating rate of marital dissolution and the increasingly complex social fabric of contemporary society. In practice, decisions regarding custody (ḥaḑānah) remain largely anchored in normative-textual paradigms—such as the child’s age or the presumed primacy of maternal care—without holistically evaluating the principle of the best interests of the child. This gap between legal norms, Pancasila values, and the lived realities of Indonesian families calls for critical reassessment. This research seeks to reconstruct the best interests of the child principle within Religious Court proceedings through an integrative framework that draws upon Pancasila values and Islamic Sociological Jurisprudence theory. A qualitative methodology combining normative-juridical and socio-legal approaches is employed, encompassing statutory analysis, judicial decision review, and engagement with relevant scholarly literature. Findings indicate that the application of the best interests principle remains fragmented, insufficiently addressing psychological, sociological, and cultural dimensions. The proposed reconstruction foregrounds the integration of humanitarian values, social justice, and divine principles enshrined in Pancasila alongside a contextually adaptive Islamic legal methodology. This envisions judges not merely as law appliers, but as agents of social equity who champion the comprehensive well-being of children. This study concludes that a reconstructive paradigm grounded in Pancasila and Islamic Sociological Jurisprudence can substantially enhance child rights protection and facilitate judicial outcomes that are more equitable, compassionate, and oriented toward children’s flourishing.